2016
DOI: 10.1186/s12938-016-0157-2
|View full text |Cite
|
Sign up to set email alerts
|

Several insights into the preprocessing of electrograms in atrial fibrillation for dominant frequency analysis

Abstract: BackgroundDominant frequency (DF) analysis of atrial electrograms has become an important method in characterizing atrial fibrillation (AF). As a classic method, Botteron’s approach is widely used in the preprocessing of frequency analysis during AF. It includes three steps: (1) band-pass filtering at 40–250 Hz, (2) absolute value, and (3) low-pass filtering at 20 Hz. This paper aims to expound the necessity and adjustability of each step.Methods and resultsUnipolar epicardial mapping signals were recorded dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We investigated the effect of altering pre-processing steps on extracting HDFs as proposed by Li and colleagues [ 25 ], namely filtering the VEGMs between 20 and 100 Hz and rectifying these filtered signals. We examined the effect of estimating the AF spectral content using Welch's method and the FFT method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the effect of altering pre-processing steps on extracting HDFs as proposed by Li and colleagues [ 25 ], namely filtering the VEGMs between 20 and 100 Hz and rectifying these filtered signals. We examined the effect of estimating the AF spectral content using Welch's method and the FFT method.…”
Section: Methodsmentioning
confidence: 99%
“…An elaborate intuition on how to derive and interpret HDFs from endocardial data has been presented by Ng and Goldberger in a series of publications [ 20 , 23 , 24 ]. Further recommendations on deriving frequency spectra using Welch periodograms [ 4 ] and optimal pre-processing steps for unipolar electrograms were recently presented [ 25 ]. Following these recommendations, it was shown that dominant frequency (DF) analysis could be performed reliably on both unipolar and bipolar endocardial signals [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we would get the absolute value of the outputs from previous procedure, and finally the signal would pass a third-order Butterworth filter with a 20 Hz cutoff. After such processing, the ventricular activity can be greatly suppressed [22].…”
Section: B Data Preprocessing 1) Filtering Of Bspmsmentioning
confidence: 99%
“…But it was firstly proposed as the assessment of the spatial organization by means of a cross-correlation approach [21]. In our previous study [18], [22], we applied Botteron's approach to BSPM signals as a rhythm analysis tool. In this study, we modified the Botteron's approach to apply it to the derived AF signals in order to obtain rhythm-related indicator waveform for further lead selection.…”
Section: Adapted Botteron's Approachmentioning
confidence: 99%
“…Based on the spectral content of derived AF signals and the theoretical basis of Botteron's approach [22], each step of Botteron's approach was modified. The signals were firstly band-pass filtered using a digital, zero-phase, third-order Butterworth filter with the range of 4-60 Hz instead of 40-250Hz.…”
Section: Adapted Botteron's Approachmentioning
confidence: 99%